Development of Web-Based Information System to Support Personal Trainers’ Performance in Medan - Alginda Pranata Tarigan; Imran Akhmad; Afri Tantri (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The project objective is to design a web-based information system that is aimed at recording the training programs and body composition of clients and improve the performance of personal trainers in Medan City. Manual recording systems, because they are more error prone and difficult to analyze or give real-time feedback, become the key problem for personal trainers. It adopted Research and Development (R&D) approach to research using 4D development model (Define, Design, Develop and Disseminate). The user-generated product Trainer Track has features such as digital exercise log, body composition tracking, and visualization of the user’s progress. The feasibility of the system was supported by two expert validation and field operation using 25 personal trainers from the fitness centres of Medan. Results It showed that the system reached a feasibility level of 94.75%, rated as highly feasible. These findings indicate that the use of a web-based information system can lead to a much more efficient work, higher accuracy data collection and the empowerment of the personal trainers to run a personalized data based training service.